Identification of Peach NAP Transcription Factor Genes and Characterization of their Expression in Vegetative and Reproductive Organs during Development and Senescence - Li, Fang; Li, Jinjin; Qian, Ming; Han, Mingyu; Cao, Lijun; Liu, Hangkong; Zhang, Dong; Zhao, Caiping (Frontiers in Plant Science, 2016)
The NAP (NAC-like, activated by AP3/P1) transcription factor belongs to a subfamily of the NAC transcription factor family, and is believed to have an important role in regulating plant growth and development. However, there is very little information about this subfamily in Rosaceous plants. We identified seven NAP genes in the peach genome. PpNAP2 was categorized in the NAP I group, and contained a conserved transcription activation region. The other PpNAP genes belonged to the NAP II group. The expression patterns of the PpNAP genes differed in various organs and developmental stages. PpNAP1 and PpNAP2 were highly expressed in mature and senescing flowers, but not in leaves, fruits, and flower buds. PpNAP3 and PpNAP5 were only expressed in leaves. The PpNAP4 expression level was high in mature and senescing fruits, while PpNAP6 and PpNAP7 expression was up-regulated in mature and senescent leaves and flowers. During the fruit development period, the PpNAP4 and PpNAP6 expression levels rapidly increased during the S1 and S4 stages, which suggests these genes are involved in the first exponential growth phase and fruit ripening. During the fruit ripening and softening period, the PpNAP1, PpNAP4, and PpNAP6 expression levels were high during the early storage period, which was accompanied by a rapid increase in ethylene production. PpNAP1, PpNAP4, and PpNAP6 expression slowly increased during the middle or late storage periods, and peaked at the end of the storage period. Additionally, abscisic acid (ABA)-treated fruits were softer and produced more ethylene than the controls. Furthermore, the PpNAP1, PpNAP4, and PpNAP6 expression levels were higher in ABA-treated fruits. These results suggest that PpNAP1, PpNAP4, and PpNAP6 are responsive to ABA and may regulate peach fruit ripening.